2021
DOI: 10.3390/nu13093197
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Postprandial Gut Hormones and Markers of Bone Remodeling

Abstract: Gut-derived hormones have been suggested to play a role in bone homeostasis following food intake, although the associations are highly complex and not fully understood. In a randomized, two-day cross-over study on 14 healthy individuals, we performed postprandial time-course studies to examine the associations of the bone remodeling markers carboxyl-terminal collagen type I crosslinks (CTX) and procollagen type 1 N-terminal propeptide (P1NP) with the gut hormones glucose-dependent insulinotropic polypeptide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
(53 reference statements)
2
3
0
Order By: Relevance
“…In line with prior results ( 28 , 50 ), no significant association between serum sodium levels and BMD was observed in this study. This may be attributable to the inability of BMD values to accurately recapitulate bone changes in patients with T2D ( 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…In line with prior results ( 28 , 50 ), no significant association between serum sodium levels and BMD was observed in this study. This may be attributable to the inability of BMD values to accurately recapitulate bone changes in patients with T2D ( 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although the present study observed an independent positive correlation between the LDL-C/Apo B ratio and BTMs, we failed to observe a correlation between the LDL-C/Apo B ratio and T-score. This was similar to other studies ( 26 , 41 ), which might ascribe to the fact that BMD or T-score could not fully reflect bone alternations in T2D.…”
Section: Discussionsupporting
confidence: 91%
“…Decreased levels of the propeptide of type I procollagen and osteocalcin have negative effects on bone structure and mineralization in broilers ( Szulc et al, 2017 ). Moreover, gastrointestinal hormones are typically related to bone resorption-related markers and affect bone homeostasis ( Jensen et al, 2021 ). Increased AKP activity is primarily related to increased osteoblastic activity in broilers, and can be treated as a positive marker to evaluate bone health ( Asensio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%